Assessments of the impacts of land use/land cover change on water resources: Tana Sub-Basin, Ethiopia - Bewuketu Abebe Tesfaw; Bloodless Dzwairo; Dejene Sahlu (Journal of Water and Climate Change, 2023)
Change detecting land use/land cover helps assess and quantify its impact on water resources. This study aims to assess the impacts of land-use/land-cover change on water resources using the SWAT model in the Tana sub-basin, Ethiopia. The research detects and presents the changes between three LULC maps (1986, 2000, and 2014). The results suggest that over the last 28 years, the water body is the least disturbed and sub-afroalpine vegetation is the most transformed in terms of coverage. Cultivated lands gained a large area of cover from the other types. Most of the vegetation cover showed a decreased trend. Forest land and grassland decreased continuously while wetland showed a small variation compared to the other cover types. On the other hand, bush and shrubland recorded about a 1% increase in the total area and an unexpected fast decline in the second period. LULC changes would have an impact on water resources in the study area. The average annual water yield increased by 14.88 and 12.6%, baseflow increased by 18.4% and decreased by 7.16%, surface runoff increased by 12 and 16.16%, evapotranspiration decreased by 18.39 and 13.49%, for 2000 and 2014, respectively, compared to baseline 1986. HIGHLIGHTS The impact of land-use/land-cover change on water resources is assessed in the Tana sub-basin.; The study analysis indicated that the changes in LULC have implicated effects on the water balance components using SWAT.; The approach used has accredited contributions and provides perceptible information that will allow stakeholders and decision-makers to make prominent choices regarding natural resource planning and management.;